The nature and potential of industrial development within the Southern African Development Community (SADC) and the facilitating role of trade liberalisation and foreign direct investment in selected countries - Mutambara, Tsitsi Effie (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2026)
To date the SADC region has managed to develop a manufacturing base but this base is still small as evidenced by its low contribution to GDP. For example, only three out of the fourteen SADC countries, viz. Mauritius, South Africa and Swaziland, had over 20 percent of their GDP originating from the manufacturing sector throughout the 1990s. Also to note is that while the manufacturing sector is quite diversified, the sector is dominated by industrial processes which are more of resource and labour-intensive in nature than those processes of scale-intensive, differentiated and science based in nature. TIle trade performance of the manufacturing sector supports these observations and as such the region is heavily dependent on imports for scale-intensive, differentiated and science based commodities. However, despite the fact that the region tends to focus more on resource- and labour-intensive manufacturing activities, products from these manufacturing activities are still significant components of manufactured goods imports into the region. Also to note is that since resource- and labour-intensive industries dominate manufacturing activities
Keywords: Southern African Development Community; Investments, Foreign -- Africa, Southern; Free trade -- Africa, Southern; Economic development -- Africa, Southern; Industrialization -- Africa, Southern; Industrial policy -- Africa, Southern; Africa, Southern -- Economic policy